PEMETAAN PERUBAHAN (MUTASI) VIRUS HEPATITIS B - Tonang DA; Rina AS; JB Suparyatmo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
Recently, the issue of Hepatitis B Virus (HVB) mutation is becoming a significant point to consider. The mutation might rendersignificant problems as the virus might escape from the detection method, vaccination induced-protection and treatment modalities. Thestudy was to analyze the profile of serological parameters in the HVB infected serum in Surakarta. As many as 36 HBsAg-positive serawere randomly retrieved from the patients in Moewardi Hospital and donors in Blood Bank of Indonesian Red Cross (PMI) in Surakartaduring August-September 2007. Having analyzed by immunoanalyzer, 13 (36.1%) of 36 sera were HBeAg-positive suggesting an activeinfection and potent of transmission. Interestingly, 3 (8.3%) of 36 sera were Anti-HBs-positive, while the other 5 (13.8%) showeddetected level of Anti-HBs even lower than the cut-off (12 mIU/ml). Accordingly, 22 (61.1%) of 36 serum were Anti-HBe-positive, whileone (2.8%) sera was HBe-Ag-positive as well as Anti-HBe-positive. The data suggested some possibilities: double infection with two ormore subtypes of HBV, mutation resulting in quasi-species phenomenon, or the so-called healthy carrier. More extensive and specificstudies are necessary to confirm and elucidate the profile.